Trade Deficit with China – an Issue for the Euro Area? - Klaus Weyerstrass (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The rise of China in the world economy and its growing importance as investor in industrialised and developing countries raised concerns of policy makers in some countries. The large deficit in the trade with China has caused the US government to increase tariffs on imports from China. Contrary to the situation regarding trade between China and the US, trade between the euro area aggregate and China is almost balanced, with a small deficit in trade with goods and a small surplus in the services balance of the euro area. On the individual country level, Germany, Ireland and Finland record trade surpluses with China. An econometric analysis identified domestic demand as the most important determinant of the trade balance between the euro area and China. Also revealed comparative advantages, the exchange rate between the euro and the renminbi as well as the stance of fiscal policies influence the trade balance. Since trade between the euro area and China is more or less balanced, there is no need for policy actions to address any imbalances. Furthermore, for open economies which many of the euro area countries are, openness to international trade is important. Thus, European policy makers are well advised to advocate free market access, but reciprocity is important.
Keywords: 330